Spatial organization of long-term depression in mouse hippocampal schaffer collateral : CA1 synapses. - Chan, Jasmine Ee Teng. (2009)
Long-term depression (LTD) is a form of long-lasting synaptic plasticity that has been postulated to serve as a neural mechanism for memory and learning. However, the representation of LTD within neural circuitry remains poorly understood. To study LTD at the level of neural circuitry, I adopted voltage-sensitive dye imaging (VSDI) to acquire optical signals of transmission at Schaffer Collateral – CA1 synapses from living hippocampal slices. Following low-frequency stimulation LFS), optical responses showed a decrease in peak amplitude that lasted for more than 60 min. LFS-evoked LTD was found to be dependent on the activation of Nmethyl- D-aspartic acid (NMDA) receptors because it was blocked by 2-amino-5-phosphonovaleric acid (APV), an antagonist of these receptors. Interestingly, the spatial distribution of LTD was not identical to that of responses to single synaptic stimuli. Instead, a heterogeneous spatial distribution for LTD was observed. This novel observation of LTD representation within neural circuitry will hopefully provide insights towards the role of synaptic plasticity in memory and learning in the future.